Comparing the appropriateness of antimicrobial prescribing among medical patients in two tertiary hospitals in Malaysia - Loong, Ly Sia; Siew Mei Lai, Pauline; Jamaluddin, Nurul Adilla Hayat; Naina-Mohamed, Isa; Periyasamy, Petrick; Lau, Chee Lan; Thursky, Karin; James, Rodney; Ponnampalavanar, Sasheela; The Malaysian NAPS Working Group (The Journal of Infection in Developing Countries, 2022)
Introduction: Malaysia is an upper-middle-income country with national antimicrobial stewardship programs in place. However, hospitals in this country are faced with a high incidence of multidrug-resistant organisms and high usage of broad-spectrum antibiotics. Therefore, this study aimed to use a standardized audit tool to assess clinical appropriateness, guideline compliance, and prescribing patterns of antimicrobial use among medical patients in two tertiary hospitals in Malaysia to benchmark practice. Methodology: A prospective hospital-wide point prevalence survey was carried out by a multidisciplinary team in April 2019 at the University Malaya Medical Centre (UMMC) and the Hospital Canselor Tuanku Muhriz (HCTM), Kuala Lumpur, Malaysia. Data was collected from the patient’s electronic medical records and recorded using the Hospital National Antimicrobial Prescribing Survey toolkit developed by the National Centre for Antimicrobial Stewardship, Australia. Results: The appropriateness of prescriptions was 60.1% (UMMC) and 67% (HCTM), with no significant difference between the two hospitals. Compliance with guidelines was 60.0% (UMMC) and 61.5% (HCTM). Amoxicillin-clavulanic acid was the most commonly prescribed antimicrobial (UMMC = 16.9%; HCTM = 11.9%). Conclusions: The appropriateness of antimicrobial prescribing in medical wards, compliance with guidelines, and prescribing patterns were similar between the two hospitals in Malaysia. The survey identified several areas of prescribing that would need targeted AMS interventions.